Noting down internal dimensions of the Bisaldeo Temple - Temples of India Project Team (Jio Institute, 2024)
Ar. Ankita Peshin drawing proportionate elevation sketches to note internal dimensions of Bisaldeo Temple, Tonk district, Rajasthan. (Image courtesy: Vrinda Dhiman)